Different Surgical Techniques in Tubo-ovarian Abscess Management - Hale GÖKSEVER ÇELİK; Engin Çelik; Semra Yüksel; Ercan Baştu; Hasan Cemal Ark (Medical Network, 2017)
Objectıve: Tubo-ovarian abscess is mostly a consequence of pelvic inflammatory disease. We aimed to compare success of the different surgical methods in tubo-ovarian abscess treatment. Study Design: 53 patients with Tubo-ovarian abscess that were hospitalized and operated in the Department of Obstetrics and Gynecology at Kanuni Sultan Suleyman Training and Research Hospital during one year were included. Patients who had underwent salpingectomy/salpingo-oophorectomy and only abscess drainage were compared. Results: Salpingectomy/salpingo-oophorectomy had been done in 74.5% of cases and only drainage had been applied in 25.5% of cases. Difference in mean values between 2 groups were not observed except white blood cell count. Conclusıon: Treatment of Tubo-ovarian abscess must be a combination of parenteral antibiotics and early surgical procedure to prevent poor outcomes. There is not any difference between different surgical techniques. But additionally more studies are needed to better understand which operation technique is more effective and less complicated.